2017
DOI: 10.1016/j.pmn.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Education Interventions for Managing Acute Pain in Hospital Settings: A Systematic Review of Clinical Outcomes and Teaching Methods

Abstract: Objectives: To examine the effects of nursing education interventions on clinical outcomes for acute pain management in hospital settings, relating interventions to healthcare behavior-change theory. Methods Results:The twelve eligible studies used varied didactic and interactive teaching methods.Several studies had weaknesses attributable to selection biases, uncontrolled confounders, and lack of blinding of outcome assessors. Studies did not explicitly reference theory underlying design of their interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
1
25
0
6
Order By: Relevance
“…Work-related factors also influence the quality of process outcomes. It has been suggested that aspects like emotions, professional recognition, and work load do have an influence [48]. While emotions depend on the individual's situation and hospitals as employers might provide programs to cope with such conditions, the nursing profession suffers a lack of attractiveness with impact on motivation [49].…”
Section: Processes: Reliable and Efficient!mentioning
confidence: 99%
“…Work-related factors also influence the quality of process outcomes. It has been suggested that aspects like emotions, professional recognition, and work load do have an influence [48]. While emotions depend on the individual's situation and hospitals as employers might provide programs to cope with such conditions, the nursing profession suffers a lack of attractiveness with impact on motivation [49].…”
Section: Processes: Reliable and Efficient!mentioning
confidence: 99%
“…Drake and Williams9 conducted a systematic review of educational interventions used in acute hospital settings to improve pain management. The studies (n=12) they appraised gave unhelpfully brief descriptions of the educational intervention, but these included web-based evidence guidelines, teaching sessions, audit and feedback, a pocket pain assessment guide and a computer decision-support system.…”
Section: Key Messages From the Twitter Chat (#Ebnjc)mentioning
confidence: 99%
“…In Drake and Williams’ systematic review,9 the outcome measures included completion of pain assessment documentation, use of a pain assessment tool, mean pain rating of a patient group and reduction in the percentage of patients reporting moderate to severe pain as well as one study that used pre-knowledge and post-knowledge scores. One of the criticisms of evaluation of teaching interventions is an over-reliance on pre-knowledge and post-knowledge testing, which does not reflect any changes in practice.…”
Section: Key Messages From the Twitter Chat (#Ebnjc)mentioning
confidence: 99%
“…Recent studies report that patient characteristics (eg, age and gender) and perceived cultural stereotypes can affect pain management (Alabas, Tashani, Tabasam, & Johnson, ; Koren et al, ; Kvachadze, Tsagareli, & Dumbadze, ; Samulowitz, Gremyr, Eriksson, & Hensing, ). Thus, nurses' attitudes and views to pain management warrant exploration within the context of the social workplace (Drake & Williams, ). This is especially true for the postsurgical setting to ensure patients' pain is adequately treated.…”
Section: Introductionmentioning
confidence: 99%